Phenomenology - Gallagher, Shaun. author. aut Link
XIII, 237 p.
Keywords: Shaun Gallagher offers an exciting contemporary perspective of the subject by retrieving many important insights made by the classic phenomenological philosophers, updating some of these insights in innovative ways, and showing how they directly relate to ongoing debates in philosophy and psychology.